Optimization of Rosa roxburghii Tratt pomace fermentation process and the effects of mono- and mixed culture fermentation on its chemical composition - Yi, Xinxin; Zhang, Shuo; Meng, Duo; Zhang, Jian; Lai, Chencen; Zhang, Min; Sun, Xiaodong; Yu, Haoxiang; Wang, Pengjiao; Gao, Xiuli (Frontiers in Nutrition, 2024)
BackgroundRosa roxburghii Tratt pomace (RRTP) contains valuable components like polyphenols and polysaccharides, which have high utilization value. Fermentation is an effective technique for creating beneficial nutrients that can improve the taste, appearance, and nutritional benefits of foods. Nevertheless, there is a lack of research on the alterations in chemical composition of RRTP during fermentation.Objective and MethodsThis study aimed to ferment RRTP using Bacillus subtilis and Saccharomyces cerevisiae to improve its chemical composition. The optimal fermentation conditions for RRTP were determined through single-factor experiments and Box–Behnken design (BBD). Total phenols, total flavonoids, total triterpenes, ellagic acid, and vitamin C levels were higher in the fermented group with different strains and in the optimized group with mixed bacteria post-fermentation compared to the uninoculated group. Fermentation with different strains led to an increase in the ABTS radical scavenging capacity, DPPH radical scavenging capacity, and total antioxidant capacity (T-AOC) of RRTP.ConclusionThe HPLC-ESI-Q-Exactive Plus Orbitrap-MS method identified 20 compounds before fermentation and 34 compounds after optimized fermentation with mixed bacteria. The levels of polyphenols, flavonoids, and triterpenoids increased after the optimization with mixed bacteria. This research offers a potential approach to enhance the nutritional profile of RRTP and utilize it for the production of high-value food or feed materials.